Childcare costs and the demand for children: Evidence from a nationwide reform - Eva Mörk; Anna Sjögren; Helena Svaleryd (Center for Economic Studies and ifo Institute (CESifo), 2010)
Exploiting the exogenous variation in childcare costs caused by a Swedish childcare reform, we are able to identify the causal effect of childcare costs on fertility in a context in which childcare enrollment is almost universal, user fees are low, and the labor force participation of mothers is very high. Anticipation of a reduction in childcare costs increased the number of first births, but only seemed to affect the timing of second births. We find a negative income effect for families with children already enrolled in child care.
Keywords: H31; J13; 330; childcare; cost of children; fertility; quasi-experiment; difference-in-differences; Kinderbetreuung; Reform; Kosten; Frauenerwerbstätigkeit; Fruchtbarkeit; Feldforschung; Schweden